Preparation of ZnO/TiO2 Nanocomposite Sensitized Mangosteen Rind (Garcinia mangostana L) Dye for Light Harvesting Efficiency in Solar Cell - Utomo, Arya Dwi Cahyo; Wihadi, Muh. Nur Khoiru (Indonesian Journal of Chemical Research, 2022)
The preparation of ZnO/TiO2 nanocomposite is done using the sol-gel method for light harvesting in dye-sensitized solar cell (DSSC). The titanium dioxide (TiO2) compound was added with different ratios to the ZnO matrix and measured its effect on solar cells based on the DSSC system. The powder X-ray diffractions of nanocomposite revealed anatase (TiO2) and wurtzite (ZnO) phases have the highest peak at 25.26° and 36.97°, respectively. The energy gap was observed by diffuse reflectance-ultra violet (DR-UV) spectroscopy and it revealed that the optimum performance of nanocomposite was 3.16 eV for the 1:2 ratio. The optimum power efficiency was 2.4% with 3.6 cm2 active area, Voc= 788 mV and Isc=3.39 mA, respectively. The scanning electron microscope-energy dispersive X-ray (SEM-EDX) demonstrated the diversity of surface morphology depends on the ratio of TiO2 in the nanocomposite. This shows the addition of TiO2 to the ZnO matrix influenced the structure of the nanocomposite, which can be applied as DSSC electrodes.